2015
DOI: 10.3168/jds.2014-8940
|View full text |Cite
|
Sign up to set email alerts
|

Estrus traits derived from activity measurements are heritable and closely related to the time from calving to first insemination

Abstract: The aim of this study was to estimate genetic parameters for estrus-related traits that could improve selection for increased fertility due to improved ability of the cow to return to cycling and go into heat after calving. We compared the time from calving to first insemination (CFI) to 3 physical activity traits: the interval from calving to first high activity (CFHA), estrus duration (ED), and estrus strength (ES). We calculated CFI based on data from commercial Holstein herds that included the insemination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 30 publications
(49 reference statements)
7
35
1
Order By: Relevance
“…Other activityderived traits described by Løvendahl and Chagunda (2009) were period of increased activity and strength of estrus, which exhibited low heritabilities of 0.02 to 0.08 and 0.04 to 0.08, respectively. Ismael et al (2015) noted strong genetic correlations for interval from calving to first high activity with the traditional ICF measure (0.96). As well, moderate correlations for estrous duration and estrous strength with ICF were estimated (−0.38 and −0.50, respectively;Ismael et al, 2015).…”
Section: Estrous Expression and Activity Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other activityderived traits described by Løvendahl and Chagunda (2009) were period of increased activity and strength of estrus, which exhibited low heritabilities of 0.02 to 0.08 and 0.04 to 0.08, respectively. Ismael et al (2015) noted strong genetic correlations for interval from calving to first high activity with the traditional ICF measure (0.96). As well, moderate correlations for estrous duration and estrous strength with ICF were estimated (−0.38 and −0.50, respectively;Ismael et al, 2015).…”
Section: Estrous Expression and Activity Traitsmentioning
confidence: 99%
“…Ismael et al (2015) noted strong genetic correlations for interval from calving to first high activity with the traditional ICF measure (0.96). As well, moderate correlations for estrous duration and estrous strength with ICF were estimated (−0.38 and −0.50, respectively;Ismael et al, 2015).…”
Section: Estrous Expression and Activity Traitsmentioning
confidence: 99%
“…In this thesis, the genetic correlation between C-LA and CI varied from 0.26 to 0.31. Ismael et al, (2015) also found a positive correlation between CFHA and CFS (0.96). This indicates that selection for a shorter interval from calving to resumption of ovarian activity would benefit overall fertility.…”
Section: Breeding For Fertilitymentioning
confidence: 69%
“…The low heritability of classical fertility traits makes selection for fertility less effective. Studies of physical activity derived traits e.g., the interval from calving to the first sign of high activity (CFHA) have reported higher heritability, ranging from 0.12 to 0.18 (Løvendahl and Chagunda, 2009;Ismael et al, 2015). Though CFHA has been suggested as a measure for resumption of ovarian activity, Ismael et al, (2016) showed that a drawback is that activity monitor derived fertility traits are seasonally sensitive.…”
Section: Breeding For Fertilitymentioning
confidence: 99%
See 1 more Smart Citation